On a nonlinear equation unsolved with respect to the levy laplacian - Feller, M. N. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We propose a method for the solution of the nonlinear equationf(U(x),ΔU(x))=F(x) (Δ L is an infinite-dimensional Laplacian, Δ L U(x)=γ, γ≠0) unsolved with respect to the infinite-dimensional Laplacian, and for the solution of the Dirichlet problem for this equation.